The Issue of Islamic Education Politics in Realizing Muslim Identity in Modern Islamic Boarding School - Hamonangan, Domu; Salminawati, Salminawati; Usiono, Usiono; Rusdi, Muhammad (Jurnal Educative: Journal of Educational Studies, 2024)
This research focused on the political issues of Islamic education in contemporary Islamic boarding schools, particularly in the process of forming Muslim identity. Secularism, as a paradigm underlying the modernization of education in Indonesia, influenced national education policy, including policies regarding Islamic boarding schools. One of the main problems was the poor quality of teachers in Islamic educational institutions, which was exacerbated by the dominance of secular policies in the national education system. The aim of this research was to examine how secularism as an educational paradigm impacted modern Islamic boarding schools, as well as how the quality of teachers influenced the formation of Muslim identity in the Islamic boarding school environment. The method used was a literature review or library study, where the researcher examined relevant literature on secularism in education, teacher quality, and the political dynamics of Islamic education. The research results indicated that secularism in education tended to overlook fundamental Islamic values in the curriculum of Islamic boarding schools, making it difficult for these institutions to maintain their Islamic identity. The struggle to produce a competitive Muslim generation that adhered firmly to Islamic principles was also hindered by the low quality of teachers. The implication was that teachers and Islamic boarding schools should be given more freedom to create curricula that aligned with Islamic principles and met the demands of the times. Penelitian ini berkonsentrasi pada isu-isu politik pendidikan Islam di pondok pesantren kontemporer, terutama dalam proses pembentukan identitas Muslim. Sekularisme sebagai paradigma yang mendasari modernisasi pendidikan di Indonesia memengaruhi kebijakan pendidikan nasional, termasuk kebijakan pesantren. Salah satu masalah utama adalah kualitas guru yang buruk di institusi pendidikan Islam, yang diperparah oleh dominasi kebijakan sekular dalam sistem pendidikan nasional. Tujuan dari penelitian ini adalah untuk melihat bagaimana sekularisme sebagai paradigma pendidikan berdampak pada pesantren modern, serta bagaimana kualitas guru mempengaruhi pembentukan identitas Muslim di lingkungan pesantren. Metode yang digunakan adalah penelitian pustaka atau studi pustaka, di mana peneliti mengkaji literatur yang relevan mengenai sekularisme dalam pendidikan, kualitas guru, dan dinamika politik pendidikan Islam. Hasil penelitian menunjukkan bahwa Sekularisme dalam pendidikan cenderung mengabaikan nilai-nilai Islam yang mendasar dalam kurikulum pesantren, yang membuat sulit bagi pesantren untuk mempertahankan identitas keislaman mereka. Perjuangan untuk menghasilkan generasi Muslim yang kompetitif dan berpegang teguh pada prinsip Islam juga dihambat oleh kualitas guru yang rendah. Implimkasinya adalah kepada guru dan pesantren harus diberi lebih banyak kebebasan untuk membuat kurikulum yang sejalan dengan prinsip Islam dan sesuai dengan tuntutan zaman.